THE ROLE OF FOOTBALL IN PHYSICAL EDUCATION: DEVELOPMENT, IMPACT, AND FUTURE TRENDS - Ali Maksat; Assaubek Samat; Kartenbayev Kanat; Medeubayev Erlan; Murat Aktilek (Modern Scientific Technology, 2025)
Football is one of the most widely practiced sports globally and has a significant role in the development of physical education programs at all levels. This paper explores the role of football in promoting physical fitness, mental well-being, and social integration among students in educational institutions. It examines modern training techniques, the inclusion of football in physical education curricula, and its impact on physical, psychological, and cognitive development. The article also investigates how football fosters teamwork, discipline, and leadership skills. The study emphasizes the long-term benefits of football for personal growth and academic performance